An evaluation of the integration of indigenous musical arts in the Creative and Performing Arts syllabus and the implementation thereof in the primary schools curriculum in Botswana - Hinch, John de Courteille (University of Pretoria, 2013)
Thesis (DMus)--University of Pretoria, 2008.